Chronic diseases: Origin and cell mechanisms involved: Chronic diseases - Martínez-Puente, David Hernán; Rodríguez-Roque, Carlos Saúl; Flores-Zavala, Laura Mireya; Pérez-Trujillo, José Juan; Villanueva-Olivo, Arnulfo; Rodríguez-Rocha, Humberto; García-García, Aracely; Saucedo-Cárdenas, Odila; Montes De Oca-Luna, Roberto; Loera-Arias, María de Jesús (Cellular and Molecular Biology, 2023)
Chronic diseases are a worldwide health problem directly related to society, lifestyle, and the development of unhealthy habits over time. Cardiovascular disease, cancer, chronic respiratory disease, and diabetes are the main causes of death. Environmental factors, such as air pollutants, poor diet, genetic predisposition, or a combination of these, are related to the development of these diseases. These factors activate cell mechanisms, such as DNA damage, oxidative stress, endoplasmic reticulum stress, autophagy, inflammation, and cell death. Depending on the dose and duration of exposure to causative agents, this cell damage can be acute or chronic. Activating these cell mechanisms can rescue normal cell function and cause permanent damage, unleashing the degeneration of tissues and organs over time. A wide variety of treatments help control chronic diseases; however, they cannot be cured completely. This fact leads to complications, dysfunctions, and disabilities. Herein, we discuss some of the principal mechanisms involved and how cellular stress can lead to these diseases when they persist for a long time.